Fuzzy semi-active damping force estimator (fSADE) and skyhook semi-active suspension systems. (1st January 2011) - Abu Bakar, Saiful Anuar; Jamaluddin, Hishamuddin; Rahman, Roslan Abd.; Samin, Pakharuddin Mohd.; Masuda, Ryosuke; Hashimoto, Hiromu; Inaba, Takeshi
This paper presents the comparative study on semi-active suspension controlled by skyhook algorithm and fuzzy semi-active damping force estimator (fSADE). The damping element used in the semi-active suspension is non-pressurised magnetorheological (MR) damper. The performance of magnetorheological semi-active suspension system controlled by fSADE in terms of ride comfort is evaluated in comparison with normal suspension system and skyhook semi-active suspension system. The study is also focusing on the effects of the number of fuzzy rules used in fSADE algorithm performance. Other aspects studied are the current consumption used by the MR damper as well as the damper's ability to execute the damping forces as estimated by the controllers. The vehicle ride comforts are evaluated based on the vehicle's vertical motions (jerk, acceleration, displacement) and pitch motions (pitch rate and pitch angle). It is shown that magnetorheological semi-active suspension system controlled by fSADE is able to improve vehicle's ride comfort significantly compared to passive suspension and was better than the skyhook semi-active suspension system in terms of power consumption. It was also shown that the number of fuzzy rules used did affect the overall performance of the fSADE algorithm in semi-active suspension system.